Ownership shares and directors' proportion as majority shareholders on earnings management moderated by board activity - Farida Titik Kristanti; Hosam Alden Riyadh; Mohammed Ghanim Ahmed; Salsabila Aisyah Alfaiza; Evy Steelyana W; Abdalwali Lutfi; Baligh Ali Hasan Beshr (Cogent Business & Management, 2024)
This study looks into a theoretical model exploring the effects of ownership shares and directors' proportions as majority shareholders on earnings management. Furthermore, the primary objective of this research is to investigate the moderating role of board meeting frequency between ownership shares and directors' proportions as majority shareholders on earnings management. The current study employed a quantitative research methodology, using firms in Iraq from 2013 to 2018. In panel data regression, the researchers implemented three distinct models: the random effect model, the fixed effect model, and the common pooled model. The data were provided in two columns, one with control variables and one without control variables. This study also presents empirical evidence that ownership of shares by directors and majority shareholders was significant, implying that an increased number of shares possessed by directors and high majority shareholders would reduce earnings management. While the frequency of board meetings had no significant moderating effect on the relationship between director share ownership and earnings management, it did play a significant moderating role in the relationship between directors' proportion as majority shareholders and earnings management. Finally, the contribution of these empirical findings as research makes a valuable addition to the existing body of academic literature on earnings management, particularly within the context of the Iraq earnings management scenarios. It also has the potential to make a meaningful contribution towards mitigating the prevalence of earnings management practices. Moreover, it offers unique insights into the significance of corporate governance in the context of Iraqi financial institutions.
Keywords: 650; corporate governance; firm size; leverage; M-score; return on assets; return on equity